2017
DOI: 10.1186/s13568-017-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial action of methanolic seed extracts of Syzygium cumini Linn. on Bacillus subtilis

Abstract: Phytochemicals of Syzygium cumini are used for the treatment of various diseases as a traditional medicine but the mechanism behind their action is not well reported. Antimicrobial activity of methanolic seed extract of S. cumini was done by agar well diffusion assay on Bacillus subtilis and its zone of inhibition was found to be 20.06 mm in comparison to control having no zone of inhibition. MIC of S. cumini was found to be 0.3 mg/ml. Genomic DNA degradation of B. subtilis reveals apoptosis and FE-scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 25 publications
1
10
0
1
Order By: Relevance
“…Using MIC and Triplex PCR showed the time-dependent effects of these agents on bacterial DNA, with the most pronounced effects observed at 72 hours of incubation, confirmed by the absence of bacterial DNA on an ethidium bromide stained gel (1%). A previous study that examined aqueous extract of S aromaticum induced DNA fragmentation in B subtilis at 24, 48, and 72 hours of incubation reported timedependent results 42 that coincide with our findings. This indicates that the aqueous extract of S aromaticum has a pronounced effect on the degradation of DNA of S aureus accompanied by inhibition of bacterial protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using MIC and Triplex PCR showed the time-dependent effects of these agents on bacterial DNA, with the most pronounced effects observed at 72 hours of incubation, confirmed by the absence of bacterial DNA on an ethidium bromide stained gel (1%). A previous study that examined aqueous extract of S aromaticum induced DNA fragmentation in B subtilis at 24, 48, and 72 hours of incubation reported timedependent results 42 that coincide with our findings. This indicates that the aqueous extract of S aromaticum has a pronounced effect on the degradation of DNA of S aureus accompanied by inhibition of bacterial protein synthesis.…”
Section: Discussionsupporting
confidence: 92%
“…41 Other studies using field emission SEM reported that methanolic seed extracts of S cumini induced a significant variation in the size of Bacillus subtilis cells. 42 Scanning electron microscope analysis of the effects of treatment with quercetin showed that it exhibited antibacterial activity characterized by disruption of the integrity of the cell walls in both grampositive and gram-negative bacteria. 43 A bacterial apoptosis technique was used to assess the mode of action of the products tested.…”
Section: Discussionmentioning
confidence: 99%
“…The methanolic seed extract of S. cumini has been reported for antimicrobial activity against Bacillus subtilis, and the activity was associated with damaging the cell wall, reduction in bacterial cell size, and leaking of cellular contents [19].…”
Section: Resultsmentioning
confidence: 99%
“…This was done as previously reported [30] with slight modifications. Briefly, the E. coli cells were grown in TSB for 18 h, washed twice with phosphate buffer saline (PBS) and then adjusted to 10 6 CFU/mL with PBS.…”
Section: Propidium Iodide (Pi) Uptake Assay: Cell Viability Assessmentmentioning
confidence: 99%